PENGARUH MINAT KERJA DAN PENGALAMAN MAGANG TERHADAP KESIAPAN KERJA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Faradila Suyanto; Elvi Rahmi; Abel Tasman (Jurnal Ecogen, 2019)
An understanding of the world of work is not in accordance with the existing reality, many fields of development that require professional staff cannot be fulfilled by existing educational output. The deficiency is not only felt in terms of quantity and type, but also in terms of quality. work readiness is a condition that makes ready, and has the will, desire and ability to work. High work readiness is influenced by various aspects, including work interest and internship experience. The type of research used in this study is quantitative research with a descriptive approach, is one type of research whose specifications are systematically planned and structured clearly from the beginning of the design of the research. In this study which is an independent variable is the interest in work and internship experience, this research was conducted on UNP FE students who have carried out an internship experience course. Samples are taken based on probability sampling techniques: simple random sampling. The data analysis technique uses multiple regression analysis using SPSS version 20.00. The results of this study indicate that (1) Interest in work and experience of the work together jointly affects work readiness, (2) Interest in work has a positive and significant effect on work readiness, and (3)Experience has an influential internship and significance for work readiness.                                                . Keywords: work readiness, work interest and internship experience